49 Effect of hypothermia on out-of-hospital cardiac arrest patient with chronic kidney disease. (16th April 2018) - Kim, Min Woo; Ro, Young Sun; Shin, Sang Do; Song, Kyoung Jun; Hong, Ki Jeong; Park, Jung Ho
Abstract : Aim: Therapeutic hypothermia is performed to improve the OHCA patient's neurologic outcome. It is unclear whether the effect size of therapeutic hypothermia differs according to the baseline kidney function. Method: OHCA patients transported to ED from 2013 to 2015 in South Korea were analysed. OHCA Patients due to cardiac cause at age 15 or older, and who survived to admission were included. Those who did not get CPR or without information about neurologic outcome (CPC) at discharge were excluded. Main Exposure was whether therapeutic hypothermia was done at the hospital. Primary and secondary outcomes were hospital survival and CPC score. Multivariable logistic regression was used to calculate the adjusted odds ratios with 95% confidence intervals. To compare the effect size of the therapeutic hypothermia by underlying kidney dysfunction (CKD-nonHD, HD) and normal kidney function, interaction term (hypothermia*CKD) was added to the final model. Results: Totally 8170 patients were analysed. 4655 (56.98%) patients died and 3515 (43.02%) survived to discharge. Only 2118 (25.92%) had good neurologic outcome. The AOR of hypothermia were 1.70 (1.50–1.9) for the survival rate and 1.00 (0.88–1.18) for the favourable neurologic outcome. In interaction model, the AORs for survival rate of hypothermia were 1.76 (1.54–2.02), 1.27 (0.59–2.74) and 1.8 (0.60–1.96) in non-CKD, CKD-nonHD, and HD group respectively. Also, the AORs for good neurologic outcome of hypothermia were 1.08 (0.93–1.25), 0.37 (0.10–1.42) and 0.26 (0.09–0.73), respectively. Conclusion: Therapeutic Hypothermia on OHCA patients with underlying kidney dysfunction was less effective than with normal kidney function. Conflict of interest: None Funding: The study was financially supported by the Korea Centres for Disease Control and Prevention (CDC).